Financial Planning: What the Social and Brain Sciences Have to Offer - Forbes Jr, Raymond L.; Peng, Martina (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2022)
This paper addresses the potential linkage of the disciplines of financial planning and the social and brain sciences from the combined perspectives of a financial planning expert and a business psychologist. It seeks to offer practical guidance on how to utilize insights from recent research and practice in the social and brain sciences to address the issue of effective financial planning in a time of multiple widespread international crises. The article will review the traditional approach to financial planning, indicate where the profession appears to stand now, describe advances in social and brain science, and provide some practical tools for use by practicing financial planners. The paper will conclude with a summary of its key points.